PERILAKU GURU PRAKTIK SEKOLAH MENENGAH KEJURUAN BIDANG KEAHLIAN TEKNIK MESIN DALAM MELAKSANAKAN TUGAS PEMBELAJARAN PRAKTIK - -, Sudarman (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2007)
The behaviour is showed by practice teacher in doing duty of practiclearning express about capability of that practiced teacher duty. The capability of vocational high school practice teacher of machine technical in practice learning duty can be seen from his behaviourin doing duty of practice teaching both the open behaviour (be seen for example is blending demonstration) or close behaviour (canât be seen for example thinking). The capability rate of that vocational high school practice teacher in doing duty can be evaluated from discipline in process about planning, preparing, operation of practiced teaching and administration facility and practiced result.